UJI AKTIVITAS ANTI JAMUR EKSTRAK DAUN API-API (Avicennia marina VIERH) UNTUK MENGHAMBAT PERTUMBUHAN JAMUR Schizophyllum commune FRIES - Setiawan, Agus; Diba, Farah; Wardenaar, Evy (Universitas Tanjungpura, 2019)
The aim of the study was to extract Avicennia marina Vierh leaf and used for anti-fungal against Â Schizophyllum commune Fries, and to evaluate the best concentration of extract A. marina in inhibiting the growth of S.commune fungi. The leaf of A. marina was found in Bakau Kecil village in Mempawah Regency. Â The leaf was made into particle with size 40-60 mesh then extracted with methanol in ratio 1:5 (w/v). The extract of A. marina leaf was made into concentration 0%, 1%, 2%, 3%, 4%, and 5%. The extract then poured into PDA and one cell of S. commune fungi was put in the center of PDA, The bioassay of evaluation the inhibition of fungal growth was conducted on seven days. After seven days the anti-fungal activity was measured. Result of the research showed that the growth of fungi on concentration 1% was 35.62 mm; on concentration 2% was 33.17 mm and on concentration 3% was 27.09 mm. Meanwhile on concentration 4% and 5% the fungi was not growth, either from the first day until the end of bioassay at the seven days. Vice versa on control (0% concentration) the fungal growth until the all of the petri dish with average 91.40 mm. Concentration of extract A. marina leaf 4% and concentration 5% was classified in very strong anti-fungal activities. E xtract methanol of A. marina leaf with concentration 4% can be used to inhibition the S. commune fungi with very strong anti-fungal activities.Keywords : Anti fungal, Avicennia marina Vierh, leaf, Schizophyllum commune Fries, wood preservation